Developing scientific writing materials by using RDR and R2D2 - Supriyadi, Supriyadi (Technium Social Sciences Journal, 2022)
The purpose of this research was to develop the participative and collaborative scientific writing materials to develop the social and emotional intelligence among students. In an effort to reach the goal, the research model used was R2D2 and RDR. Research data were in the form of notes, corrections, comments, criticism from expert teams and practitioners of the product. Data were analyzed by domain technique and t test. The results of the effectiveness test showed that this development product had advantages compared with conventional scientific writing materials. The learning of scientific writing by utilizing this development product significantly influenced the improvement of social and emotional intelligence, the quality of learning process, and the achievement of student’s scholarly writing. The results of this study have implications that scientific writing materials that will be used in the learning process should be done in advance development process to obtain reliable and high quality teaching materials to achieve the quality of the process and as well the results of scientific writing.